Low-Cost Embedded System for Real-Time Manual Treadmill Speed Tracking and Running Game Integration - IRHAM MULKAN RODIANA; ALIYUS HEDRI; FEBRIAN JOSUA KONTU (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2026)
Manual treadmills are low-cost and widely accessible but lack electronic systems for measuring running speed, limiting their use in interactive or gamified applications. This study presents a simple embedded system that enables real-time speed tracking on a manual treadmill using a magnetic reed switch and an ESP32 microcontroller. Each roller rotation generates one pulse which is processed through an interrupt-based algorithm to compute linear speed. The data are transmitted to a custom Unity game application to control a running avatar in real time. Experimental results show an average speed error of 2.11% with an RMSE of 0.049 m/s and an end-to-end latency of 48 ± 4.9 ms. The findings indicate that the system is accurate, responsive, and suitable for low-cost exergaming and motion-based training.